2018
DOI: 10.1093/scan/nsy006
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the electrocortical response to monetary and social reward

Abstract: Affective science research on reward processing has primarily focused on monetary rewards. There has been a growing interest in evaluating the neural basis of social decision-making and reward processing. The present study employed a within-subject design and compared the reward positivity (RewP), an event-related potential component that is present following favorable feedback and absent or reduced following unfavorable feedback, during monetary and social reward tasks. Specifically, 114 participants (75 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 59 publications
6
65
0
Order By: Relevance
“…It is therefore possible that participants perceived "on the fence" feedback as 'worse' than rejection due to its relatively greater ambiguity compared to both acceptance and rejection feedback (Gu et al, 2017). Additionally, a recent study examining the monetary and social RewP using two feedback conditions (monetary gain and social 'like' vs. monetary loss and social 'dislike') found that the monetary and social RewP are only modestly correlated, suggesting that the neural systems underlying the RewP to monetary and social reward are at least partially distinct (Distefano et al, 2018;Ethridge & Weinberg, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that participants perceived "on the fence" feedback as 'worse' than rejection due to its relatively greater ambiguity compared to both acceptance and rejection feedback (Gu et al, 2017). Additionally, a recent study examining the monetary and social RewP using two feedback conditions (monetary gain and social 'like' vs. monetary loss and social 'dislike') found that the monetary and social RewP are only modestly correlated, suggesting that the neural systems underlying the RewP to monetary and social reward are at least partially distinct (Distefano et al, 2018;Ethridge & Weinberg, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The Island Getaway Task was presented using Python, and the task lasted approximately 30 minutes. The RewP elicited during Island Getaway and the LPP in other studies have both demonstrated acceptable internal consistency (Distefano et al, 2018;Ethridge & Weinberg, 2018;Moran, Jendrusina, & Moser, 2013). In the present study, split-half reliability of the ERPs in each condition was calculated using the correlation between the averages computed from odd-and even-numbered trials corrected using the Spearman-Brown prophecy formula (Nunnally & Bernstein, 1994).…”
Section: Task and Measuresmentioning
confidence: 91%
“…Given that more and more empirical findings suggested that the negative deflection elicited by the negative feedback is just a baseline response, while it is the positive feedback that elicits a positive deflection (Ma et al, 2014;Proudfit, 2015;Mühlberger et al, 2017;Wang et al, 2018), a consensus on this ERP component has been reached. Nowadays, the RewP is commonly accepted as a positive deflection maximizing between 250 and 350 ms, which is more pronounced in response to positive outcomes as compared to negative ones (Distefano et al, 2018;Glazer et al, 2018;Hassall et al, 2018;Wang et al, 2018). According to the motivational significance theory, one of the predominant theories of RewP, the RewP in the win-lose difference wave (RewP in response to losses subtracted by that elicited by wins) responds to the motivational and/or affective influence of feedback information, whose magnitude represents a rapid subjective evaluation of the feedback's motivational significance to the participants (Gehring and Willoughby, 2002;Yeung et al, 2005;Masaki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While emotion can significantly affect decision making, social contexts and social preferences can significantly shape our choices as these factors are important elements of many human experiences and interactions. Social reinforcement is a potent reward in its own right (Distefano et al, 2018;Hackel et al, 2017;Wake & Izuma, 2017) and helps to explain human aversion to inequality (Fehr & Schurtenberger, 2018;Tricomi et al, 2010). Moreover, the presence of peers influence participant's choices (Powers et al, 2018;Somerville et al, 2019;Van Hoorn et al, 2017), which seems to be the product of modulated social value signals (D. Fareri et al, 2012).…”
Section: Social Contextmentioning
confidence: 99%
“…The VS also responds to social rewards, such as social acceptance (Distefano et al, 2018;Wake & Izuma, 2017), inequity (Tricomi et al, 2010), rewards given to in-group vs. out-group members (Hackel et al, 2017), and social comparison (Bault et al, 2011). The VS plays a critical role in integrating social information by coding social context and rewards (Báez-Mendoza & Schultz, 2013).…”
Section: Social Contextmentioning
confidence: 99%